Durable ethanol steam reforming in a catalytic membrane reactor at moderate temperature over cobalt hydrotalcite - Espinal, Raúl (2014)
Ethanol steam reforming has been carried out in a catalytic membrane reactor consisting of cobalt hydrotalcite [Co2Mg4Al2(OH)16]CO3-4H2O-derived catalyst doped with potassium supported over cordierite and a composite PdeAg selective membrane. No sweep gas has been used, therefore, pure hydrogen has been obtained in the permeate stream, which has been maintained at atmospheric pressure. The configuration with the catalyst bed packed around the membrane has shown values of STP LH2, permeate mLETOH, liquid-1 gcat-1 up to 3 times higher than the observed for the staged membrane reactor, where the catalyst has been placed in-serieswith themembrane. The influence of the temperature (673-873 K), the waterethanol ratio (S/C = 1.8-3) and the retentate pressure (1-18 bar) on different performance parameters such as the hydrogen production and the pure hydrogen recovery has been evaluated. No carbon accumulation has been observed by SEM and XPS after 650 h operation.